Possibilities of the use of diatomaceous earth in the composition of dental materials: integrative review (Research, Society and Development, 2021)
Introduction: Among the advances in materials engineering for dental purposes is the inclusion of new and/or underutilized raw materials to obtain the best physical characteristics and, consequently, the clinical longevity of the products, one of these being diatomaceous earth or diatomite. Objective: Compile the main possibilities of use of diatomite in the composition of dental materials. Methodology: An integrative review was carried out, through a high sensitivity search in the databases: Medline via PubMed, Cochrane Wiley and Embase, and in the portal: BVS, using the descriptors "Diatomaceous Earth" and "Dental Materials" in English, as well as the synonym "Infusorial Earth" related with the Boolean Operator "AND". The selection of the articles found was performed using the Rayyan® application. Results: There were 51 studies found in the search. After reading the title, abstract and full article, four studies were included. There were no studies that specifically discuss the use of diatomaceous earth in different dental materials, but these studies presented the analysis of dental materials and/or biomaterials that had diatomite. The included papers were published between 2008 and 2014, all in English. Conclusion: Diatomaceous earth can be used in different types of dental materials, mainly to ensure better physical and mechanical properties, but more research is still needed to analyze its possibilities completely.